Polyphenols isolated from virgin coconut oil attenuate cadmium-induced dyslipidemia and oxidative stress due to their antioxidant properties and potential benefits on cardiovascular risk ratios in rats - Ademola Clement Famurewa; Fidelis Ebele Ejezie (Mashhad University of Medical Sciences, 2017)
Objective: Literature has confirmed the pathogenic role of cadmium (Cd) and its exposure in the induction of dyslipidemia implicated in the development and increasing incidence of cardiovascular diseases. The current study explored whether polyphenolics isolated from virgin coconut oil (VCO) prevent Cd-induced dyslipidemia and investigate the underlying mechanism of action, in rats. Materials and Methods: Rats were pretreated with VCO polyphenols (10, 20 and 50 mg/kg body weight; orally) 2 weeks prior to concurrent Cd administration (5 mg/kg) for 5 weeks. Subsequently, serum concentrations of lipid and lipoprotein cholesterol and cardiovascular risk ratios were determined. Hepatic activities of superoxide dismutase (SOD) and catalase (CAT) as well as reduced glutathione (GSH) and malondialdehyde (MDA) contents were analyzed. Results: Sub-chronic Cd administration significantly increased the serum levels of total cholesterol, triglycerides, low density lipoprotein cholesterol and very low density lipoprotein cholesterol while markedly reduced high density lipoprotein cholesterol. Hepatic activities of SOD and CAT as well as GSH content were suppressed by Cd, whereas MDA level was obviously increased. The co-administration of VCO polyphenol with Cd remarkably restored lipid profile and cardiovascular risk ratios and stabilized antioxidant defense systems comparable to control group. Conclusion: This is the first study presenting that polyphenols isolated from VCO prevent Cd-induced lipid abnormalities and cardiovascular risk ratios by improving antioxidant defense systems.